2021
DOI: 10.1186/s40001-021-00483-0
|View full text |Cite
|
Sign up to set email alerts
|

Atypical HIV-vacuolar myelopathy: a case report

Abstract: Background Here, we report an atypical HIV-vacuolar myelopathy and search the available medical literature about atypical presentations of human immunodeficiency virus associate vacuolar myelopathy (HIV-VM) and immunoglobulin therapy response. Case A 26-year-old lady who was 4 weeks postpartum presented to us with acute flaccid quadriparesis, with no sensory level. Extensive workup ruled out other causes of myelopathy. She developed a stage 3 acute… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Posterior linear hyperintensity was often observed in patients with PSA ischemia, whereas it was not found in the NMOSD group. Although similar linear lesions on T2 may be observed in acquired immunodeficiency syndrome-related vacuolar myelopathy [ 37 ], copper deficiency [ 38 ], neurosyphilis [ 39 ], nitrous oxide intoxication [ 40 ], Sjögren syndrome [ 41 ], subacute combined degeneration of the spinal cord [ 42 ], and subacute myelo-optico-neuropathy (i.e., side effects of clioquinol) [ 43 ], posterior linear DWI hyperintensity that has low-ADC values is possibly more specific for SCI due to the same aforementioned reasons. Owl’s eyes sign, pencil-like hyperintensity, and posterior linear hyperintensity can be observed on DWI with the corresponding low-ADC region and may contribute to the diagnosis of SCI.…”
Section: Discussionmentioning
confidence: 84%
“…Posterior linear hyperintensity was often observed in patients with PSA ischemia, whereas it was not found in the NMOSD group. Although similar linear lesions on T2 may be observed in acquired immunodeficiency syndrome-related vacuolar myelopathy [ 37 ], copper deficiency [ 38 ], neurosyphilis [ 39 ], nitrous oxide intoxication [ 40 ], Sjögren syndrome [ 41 ], subacute combined degeneration of the spinal cord [ 42 ], and subacute myelo-optico-neuropathy (i.e., side effects of clioquinol) [ 43 ], posterior linear DWI hyperintensity that has low-ADC values is possibly more specific for SCI due to the same aforementioned reasons. Owl’s eyes sign, pencil-like hyperintensity, and posterior linear hyperintensity can be observed on DWI with the corresponding low-ADC region and may contribute to the diagnosis of SCI.…”
Section: Discussionmentioning
confidence: 84%
“…HIV‐associated vacuolar myelopathy (HIV‐VM) is the main cause of myelopathy in patients with HIV/AIDS, ranging from 22% to 55% of the cases, worldwide. HIV‐VM is the most frequent form of spinal cord disorder in individuals with HIV, which causes damage to the myelin sheath protecting nerve cells, leading to the formation of tiny vacuoles in the nerve fibres 23,24 . This condition is progressive with spastic paraparesis, sensory ataxia, and autonomic dysfunction that resembles subacute combined degeneration observed in vitamin B12 deficiency and other neurological disorders 25 .…”
Section: Blood‐borne Viruses and Neurological Manifestationsmentioning
confidence: 99%
“…HIV-VM is the most frequent form of spinal cord disorder in individuals with HIV, which causes damage to the myelin sheath protecting nerve cells, leading to the formation of tiny vacuoles in the nerve fibres. 23,24 This condition is progressive with spastic paraparesis, sensory ataxia, and autonomic dysfunction that resembles subacute combined degeneration observed in vitamin B12 deficiency and other neurological disorders. 25 Initially, before the introduction of antiretroviral treatment in individuals with AIDS, HIV-VM was reported as a progressive condition leading to death within months of diagnosis, often accompanied by HAD.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In a trial to assess the effectiveness of IVIg in patients with VM, Cirkurel et al found lessened lower limb palsy, which may be related to IVIg's anti-inflammatory properties [ 10 ]. Based on this evidence, IVIG has been attempted in several other studies, where it is found to be effective in HAART-resistant VM cases [ 8 ], but in other studies, it is found to be ineffective [ 11 ].…”
Section: Introductionmentioning
confidence: 99%